A hybrid ant colony optimization algorithm for solving facility layout problems formulated as quadratic assignment problems - Kuan, Yew Wong (Emerald Group Publishing Limited, 2010)
Purpose – This paper aims to describe a new hybrid ant colony optimization (ACO) algorithm developed to solve facility layout problems (FLPs) formulated as quadratic assignment problems (QAPs).